Prevalence of Parasites of Medical Importance on Fruits and Vegetables Sold in Markets of Makurdi and Otukpo, Benue State-Nigeria - Apuu, Vincent kulamter; Nkanga, Itorobong Ibong; Okita, Faith Odije; Sunday, Janet (International Journal of Scientific Research in Biological Sciences, 2022)
The recovery of protozoa cysts and helminths ova from fruits and vegetables is of great public health significance. Consumption of improperly washed fresh fruits and vegetables constitutes considerable health risk and is the major route of transmission of intestinal parasites. This study aimed at determining the prevalence of parasites on edible fruits and vegetables sold in Makurdi and Otukpo metropolises, Nigeria. Samples were obtained from 3 markets per location and a total of 9 fruits and vegetables were used for the study. Sediments obtained from washing the fruits and vegetables with normal saline were centrifuged and then viewed under the microscope using x4 and x10 objectives. Eggs, cysts, and larvae of parasites including Ascaris lumbricoides (37.60%), Giardia lamblia (10.86%), Entamoeba histolytica (14.13%), Fasciola hepatica (10.86%) and Strongyloides stercolaris (22.82%) were found to be prevalent in this study across the sampled locations. There was no statistical significance between infected fruits and vegetables with markets, locations and all sampled variables in this study (p<0.05). The result from this study showed high contamination (40.4%) of fruits and vegetables sold in Makurdi and Otukpo markets in Benue State. All parasites recovered in this study are of public health importance as they have been mostly implicated to cause morbidity in man and animals. Hygienic Practices should be promoted among farmers, vendors and the public through health education, health awareness campaigns, to mitigate contamination of fruits and vegetables.